PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN TENDANGAN T ATLET PENCAK SILAT TAPAK SUCI - Muhammad Arif; Hasrat A Aimang; Nurhikmah Nurhikmah (Damhil Education Journal, 2021)
Speed in a pencak silat T kick is a very important factor to support the success in launching attacks on the opponent's body.  This study aims to determine the effect of treatment, namely plyometric training on the results of the kick speed of T pencak silat on athletes of Tapak Suci 230 pencak silat, Banggai Regency.  The research which was conducted at the Padepokan IPSI, Banggai Regency was also an experimental quantitative study with the One-group pre-test post-test research design.  Based on the overall measurement results, the data obtained from the kick speed test are: the mean value of the pre-test is 21.23 and the post-test is 28.23.  It was found that the percentage value of increase from the initial test and the final test was 36.6%.  Furthermore, by paying attention to the post-test average score of kick speed T, the athletes are categorized as “Good”.  Thus it can be concluded that in this study, the treatment given, namely plyometric training, greatly influenced the T kick speed of the Tapak Suci 230 pencak silat athlete in Banggai Regency.